The Russian Monarchist Movement in Exile: An Analytical Study of (Concept, Identity, and Political Ideas) (Al-Mostansiriyah journal for Arab and international studies, 2026)
The structural change of the Russian state at the beginning of the twentieth century produced real effects on the Russian intelligentsia, driving some of them into exile. Not just a struggle for power, but to preserve traditional Russian identity, The outcome of the transition from Tsarist Russia to Communist Russia. From the perspective of the advocates of the Russian monarchist movement, these transformations were not so much victories for the Russian state as they were setbacks in its historical trajectory. The problem addressed in this study was to demonstrate the extent to which the Russian monarchist movement in political exile succeeded in establishing a system of government in post-communist Russia. Considering the crystallization of their collective Russian identity in exile, formed from (the Church, despotism, nationalism), Between cultural rejection and intellectual interaction with the cognitive and intellectual system in the host countries, To what extent has the aforementioned current become a foundational reference for the doctrine of the Russian state and its contemporary policies? In response to the requirements of the research, the study employed a set of scientific methods to achieve the desired cognitive goals. The analytical approach formed the basic basis for intellectual treatment, while the effectiveness of other approaches emerged as supporting tributaries and procedural tools such as the descriptive approach, The comparative method ,the structural approach, and the deconstructive approach. One of the most important findings of the study is the relative success of the Russian monarchist movement in exile in establishing the system of government in post-communist Russia. It became a dynamic historical actor that refused to disappear and was not merely an echo of the past, and it was restructured in a way that was consistent with the requirements of the contemporary Russian state and the outcomes of the twenty-first century.Keywords: movement, monarchy, Russia, exile, political ideas, identity.